Bullying victimization among adolescents during the early phase of war in Ukraine : A comparative cross-sectional study in 2016-2017 - Silwal, Sanju; Westerlund, Minja; Osokina, Olga; Hinkka-Yli-Salomaki, Susanna; Hodes, Matthew; Skokauskas, Norbert; Sourander, Andre (WILEY, 2025)
Background
War profoundly impacts adolescent development and may increase the likelihood of aggressive responses when such behavior is perceived as acceptable and accessible. War may, hence, exacerbate a form of interpersonal violence already prevalent among children and adolescents.
Methods
We conducted a comparative cross-sectional study 2 years after the Russian invasion of Eastern Ukraine in 2014 by comparing the prevalence of bullying victimization among adolescents aged 11–17 years (N = 2766) in two administrative regions with different levels of wartime traumatic stressor exposure.
Results
Female adolescents in the war-affected region were bullied more often compared to those in the non-affected region [65.3% vs. 56.3%, adjusted Odds Ratio (aOR) = 1.5, 95% CI 1.2–1.9]. For both boys and girls, symptoms of psychopathology were associated with bullying victimization often [girls: depression (aOR = 2.9, 95% CI 2.4–3.4); boys: depression (aOR = 3.3, 95% CI 2.6–4.1) and PTSD (aOR = 1.7, 95% CI 1.4–2.02)]. In the war-affected region, a dose–response relationship between bullying victimization often and war-event exposure was observed in both sexes [girls: 1–3 war-events (aOR = 1.4, 95% CI 0.7–2.6), 4–6 (aOR = 2.4, 95% CI 1.3–4.5) and ≥7 (aOR = 5.5, 95% CI 2.7–11.1); boys: 1–3 (aOR = 1.4, 95% CI 0.7–2.8), 4–6 (aOR = 3.2, 95% CI 1.7–6.3), and ≥7 (aOR = 6.8, 95% CI 3.1–14.8)].
Conclusions
War exposure was associated with bullying victimization, with girls being bullied more often than boys. Bullying victimization was linked to cumulative traumatic stressor exposure in the war-affected region for both sexes.